THE CORRELATION BETWEEN THE INTENSITY OF PLAYING ONLINE GAME AND THE AGGRESSIVE BEHAVIOR OF ADOLESCENTS IN SMA MUHAMMADIYAH SOKARAJA. - Ema Putri Oktaviani; Siti nurjanah (HUMAN CARE JOURNAL, 2021)
AbstractBackground: The trend of online games needs to be concerned by Indonesian people, as many as 3 million people are active in playing games, while in America as many as 1.3 billion people play online games. In the online game, some have scenes of violence both verbal and physical. So that those conditions can cause aggressive behavior in adolescents.Objective: To find out the correlation between the intensity of playing online games and the aggressive behavior of adolescents in SMA Muhammadiyah Sokaraja.Method: This type of research is quantitative descriptive using cross sectional method. The research population was teenagers at SMA Muhammadiyah Sokaraja. The sampling technique used in this research was a total sample of 96 respondents. The analysis used chi square statistical test.Results: In this research, the results showed the intensity of playing online games mostly in the moderate category as many as 40 respondents (41.7%) and aggressive behavior was mostly in the moderate category as many as 55 respondents (57.3% ). Chi square test obtained a value (0,000 0.05) Ha is accepted, meaning that there is a correlation between the intensity of playing online games and the aggressive behavior in adolescents at SMA Muhammadiyah Sokaraja.Conclusion: There is a correlation between the intensity of playing online games and the aggressive behavior in adolescents at SMA Muhammadiyah Sokaraja